The social brain: Applying a neurological, social and cultural lens to emotional neglect in childhood - M. Catherine Maternowska (Child Protection and Practice)
Charting the Experiences of Children and Adolescents Affected by Emotional Neglect (2025) provides a much-needed primer on how emotional neglect manifests in and throughout childhood and adolescence. The book's ten chapters, each with a brief abstract that serves as a helpful roadmap, cover four different topical areas: defining and understanding emotional neglect; the role of socio-emotional learning in child development; developmental trajectories of emotional neglect from infancy to adolescence; and the long-term impacts of and interventions for emotional neglect. Moving through the chapters is an intensive review of child development from a neurological, social and cultural lens. The authors take on culture—namely the effects of our digitalised lifestyle—to demonstrate how biomedical and biopsychosocial models may be insufficient considering contemporary health issues, namely stress and addictions. The book offers a timely and updated perspective on neglect serving academics and practitioners working with children and adolescents in the field of mental health. Importantly, it untangles how childhood trauma (including emotional neglect) has intergenerational effects and in doing so advocates for the creation of public policies, family support programs, and improved therapeutic interventions.